Melioidosis - Siang Ching Chieng Raymond (WikiJournal of Medicine, 2022)
This review article is written to give a comprehensive and yet straightforward overview regarding a tropical disease named melioidosis. Besides that, this article also aims to promote awareness and research in the disease. Melioidosis is an infectious disease that ravages the tropical regions around the world. However, the awareness of this disease is lacking in developing countries. It is not even included in the WHO list of Neglected Tropical Disease. The ability of this disease to spread through air by inhalation makes it a potential agent for bioweapons, although there is no documented evidence of its use in biological warfare. There are also various gaps of research in melioidosis. A search into PubMed and Google Scholar was done by using keywords "melioidosis", "melioidosis biological agent", "Burkholderia pseudomallei", "human melioidosis", and "melioidosis review" while writing this review. Allocation of resources into the study and prevention of melioidosis will help to improve the disease burden in developing countries.